Respiratory safety of lemborexant in healthy adult and elderly subjects with mild obstructive sleep apnea: A randomized, double‐blind, placebo‐controlled, crossover study. (18th March 2020) - Cheng, Jocelyn Y.; Filippov, Gleb; Moline, Margaret; Zammit, Gary K.; Bsharat, Mohammad; Hall, Nancy
Abstract: Lemborexant is a dual orexin receptor antagonist indicated for the treatment of adult and elderly individuals with insomnia. Some current pharmacologic treatments for insomnia cause respiratory depression, a serious safety concern, particularly for individuals with obstructive sleep apnea (OSA). This phase 1, randomized, double‐blind, placebo‐controlled, two‐period crossover study examined respiratory safety parameters in individuals with mild OSA following treatment with lemborexant. Participants ( n = 39) were randomized to one of two treatment sequences, including placebo and lemborexant 10 mg. Each treatment period lasted 8 days and was separated by a washout of at least 14 days. Following single or multiple doses, there were no significant differences in mean apnea–hypopnea index for lemborexant 10 mg versus placebo (least squares mean [LSM] difference [95% confidence interval CI]: day 1, −0.03 [−2.22, 2.17]; day 8, −0.06 [−1.95, 1.83]) or peripheral capillary oxygen saturation during sleep (LSM difference [95% CI]: day 1, 0.07 [−0.31, 0.46]; day 8, 0.25 [−0.11, 0.61]). There were no significant differences versus placebo for the percentage of total sleep time during which peripheral capillary oxygen saturation was <80% (LSM difference [95% CI]: day 1, 0.002 [−0.019, 0.023]; day 8, 0.006 [−0.015, 0.026]), <85% (LSM difference [95% CI]: day 1, 0.067 [−0.124, 0.258]; day 8, 0.056 [−0.117, 0.228]) or <90% (LSM difference [95% CI]: day 1, 0.312 [−0.558, 1.181]; day 8, 0.088 [−0.431, 0.607]). The incidence of treatment‐emergent adverse events was low and similar for lemborexant and placebo. Lemborexant demonstrated respiratory safety in this study population and was well tolerated.